Business Sustainability in the Era of Society 5.0: Optimizing the Utilization of Social Media and Fintech for Muslim Millennial Entrepreneurs - Nursyamsu Nursyamsu; Fitriarahayu Ningsih; Nurdin (Department of Islamic Economic Law, Institut Agama Islam (IAI) Al-Qolam, 2022)
The transformation of conventional business transactions into digital-based businesses is strongly influenced by the presence of social media and fintech. The pattern of business interactions does not only take place in traditional and modern markets, but has also penetrated the virtual world. This study aims to examine and explore efforts to optimize the use of social media and fintech for business actors from Muslim millennials in maintaining the sustainability of the business they are engaged in in the face of the Society 5.0 era. This type of research is a field research with a qualitative approach with a descriptive analysis method with a case study model on Muslim millennial business actors carried out in the Bungku Utara district, Morowali, Central Sulawesi. The result found that the use of social media in the form of Facebook, WhatsApp and Instagram as well as fintech in the form of M-Banking and E-Wallet for business continuity, plays an important role and its use in marketing, sales, market analysis, and forming and developing business networks. The theoretical implications of this research show that there is a need to integrate the use of social media and fintech in business activities by business actors. The practical implications show that the greater the use of social media in business activities, the greater the use of fintech which will support business continuity managed by business actors.